Product Quality and Price Influence Purchase Intention in Vocational High School Teaching Factories - I Putu Agus Nurjaya; Putu Guntur Pramana Putra (Pubfine Media Group, 2026)
Introduction: Vocational High Schools (Sekolah Menengah Kejuruan/SMK) are educational institutions that play an important role in preparing graduates who are ready to compete in the business and industrial sectors. The teaching factory program is one of the SMK initiatives designed as a practical learning platform that enables students to develop work skills and entrepreneurial competencies. In this context, every business entity is expected to attract consumers by offering high-quality products at competitive prices. This study aims to analyze the effect of product quality and price on purchase intention. Methods: The sampling technique used in this study was purposive sampling, also known as judgmental sampling. Based on this method, the sampling criteria included active students of SMK Pariwisata Triatma Jaya Badung in the 2024 academic period. A total of 100 students were selected as respondents. Data were processed and analyzed using the Statistical Product and Service Solutions (SPSS) software. Results: The results of the data analysis indicate that product quality (X1) has a positive and significant partial effect on purchase intention (Y). Similarly, price (X2) also shows a positive and significant partial effect on purchase intention (Y). Simultaneously, product quality (X1) and price (X2) have a positive and significant effect on purchase intention (Y). Conclusion: The findings of this study are expected to serve as a reference for future research and provide positive contributions toward the development and improvement of the Teaching Factory (TEFA) program at SMK Pariwisata Triatma Jaya Badung in the future.